1983
DOI: 10.1161/01.res.52.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Prejunctional and postjunctional actions of endogenous norepinephrine at the sympathetic neuroeffector junction in canine coronary arteries.

Abstract: SUMMARY. The effects of endogenous and of exogenous norepinephrine were studied in isolated rings of canine left circumflex coronary artery and its first ventricular branch. Norepinephrine was released from adrenergic nerve endings by transmural electrical stimulation and by tyramine. In rings contracted with prostaglandin ¥20, transmural electrical stimulation resulted in frequencydependent relaxations which were blocked by propranolol or tetrodotoxin; tyramine and exogenous norepinephrine caused concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…Miwa and Toda (1984) reported that the maximum contractions induced by KC1 were not different between in large and small coronary arteries of dogs and monkeys. The maximum constrictions produced by PGF2a were greater in large coronary arteries than in small coronary arteries of dogs (Cohen et al 1983 ;Miwa and Toda 1984). Thus, non-adrenergic constrictions induced by KCl and PGF2a were not different between in small and large coronary arteries.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Miwa and Toda (1984) reported that the maximum contractions induced by KC1 were not different between in large and small coronary arteries of dogs and monkeys. The maximum constrictions produced by PGF2a were greater in large coronary arteries than in small coronary arteries of dogs (Cohen et al 1983 ;Miwa and Toda 1984). Thus, non-adrenergic constrictions induced by KCl and PGF2a were not different between in small and large coronary arteries.…”
Section: Discussionmentioning
confidence: 73%
“…The same conclusion was reported in the helical strips of canine coronary arteries (Morishita 1979). Phenylephrine did not induce any vasoconstriction in dog and pig small coronary arteries (Bayer et al 1974;Cohen et al 1983). Those results suggested that the small arteries devoided of functioning alpha-adrenoceptors in isolated dog and pig coronary arteries (Bayer et al 1974;Cohen et al 1983).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Both linear age correlation analysis and comparison of the three different age groups showed significantly stronger contractions to noradrenaline with increasing age of the patients, which was in contrast to the contractions induced by endothelin-1 and the relaxations induced by substance P, calcitonin gene-related peptide and vasoactive intestinal peptide, which showed no significant age-dependent differences. Noradrenaline, which is released from perivascular sympathetic nerves, mediates vasoconstriction of coronary arteries via a-adrenoceptors and vasodilation via b-adrenoreceptors (Anderson et al 1972;Cohen et al 1983). The main effect of noradrenaline on the coronary artery smooth muscle has often been considered being the a 1 -and a 2 -adrenoceptormediated vasoconstriction (Vatner et al 1970, Holtz et al 1982Heusch et al 1984), whereas other studies have concluded that the b-adrenoreceptor mediated relaxation exceeds the contraction mediated by a-adrenoceptors (Ginsburg et al 1980;Corr & Burnstock 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hydroxyl radicals generated by 0.1 mM H202 plus 0.2 mM FeSO4 (Fenton reaction, Freeman & Carpo, 1982) decreased ir-ET-1, and this decrease was significantly inhibited by 10-4 M deferoxamine, a ferrous chelator, and 1200 u ml-' catalase ( Figure 7). ET-1, and PGF2a which is frequently used for the investigation of EFS-induced relaxation of blood vessels (Rooke et al, 1982;Cohen et al, 1983;Feletou & Vanhoutte, 1989). After applying EFS to Krebs-Ringer solution containing each vasoconstrictor (1 tLM AVP, 1 pIm All and 2 !LM PGF2,), the contractile activity of each vasoconstrictor was investigated on porcine coronary artery strips for PGF2, and rat aorta strips for AVP and All.…”
Section: Measurement Offree Radicals Generated By Efsmentioning
confidence: 99%